KETERAMPILAN PENGUASAAN NAHWU DAN SHARAF TERHADAP KEMAMPUAN MEMAHAI KITAB TAFSIR DI PONDOK PESANTREN MARDHATILLAH TAPANULI SELATAN - Suhartono; Zainal Efendi Hasibuan; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2024)
Nahwu science is a science that studies the arrangement and position of words in a sentence as well as the final meaning of these words. Meanwhile, neurological science is a branch of science that studies the origin of the formation of changes from one form to another. So these two knowledge are very much needed in the ability to read the book of Tafsir. The level of a person's mastery in the knowledge of nahwu sharaf will make it easier for him to read the book of Tafsir. This research is a type of field research with data collection techniques through evaluation tests. And the test measures mastery of the Nahwu-Sharaf material. Based on the analysis and discussion, the average score for the Nahwu Shorof mastery test is in the very good category